Interferon-γ and Interleukin-10 Responses during Clinical Malaria Episodes in Infants Aged 0–2 Years Prenatally Exposed to Plasmodium falciparum: Tanzanian Birth Cohort - Boniphace Sylvester; Dinah B. Gasarasi; Said Aboud; Donath Tarimo; Siriel Masawe; Rose Mpembeni; Göte Swedberg (Journal of Tropical Medicine)
Background. Infants born to mothers with placental malaria are prenatally exposed to Plasmodium falciparum antigens. However, the effect of that exposure to subsequent immune responses has not been fully elucidated. This study aimed at determining the effect of prenatal exposure to P. falciparum on Interleukin-10 and Interferon-γ responses during clinical malaria episodes in the first 24 months of life. Methods. This prospective cohort study involved 215 infants aged 0-2 years born to mothers with or without placental malaria. Enzyme-linked immunosorbent assay (ELISA) was used to determine levels of IL-10 and IFN-γ in infants and detect IgM in cord blood. Data were analyzed using SPSS version 20. Findings. Geometric mean for IFN-γ in exposed infants was 557.9 pg/ml (95% CI: 511.6-604.1) and in unexposed infants it was 634.4 pg/ml (95% CI: 618.2-668.5) (P=0.02). Mean IL-10 was 22.4 pg/ml (95% CI: 19.4-28.4) and 15.1 pg/ml (95%CI: 12.4-17.6), respectively (P=0.01). Conclusions. Prenatal exposure to P. falciparum antigens significantly affects IL-10 and IFN-γ responses during clinical malaria episodes in the first two years of life.